Chromosome number variation and phylogenetic divergence of East Asian Cirsium sect. Onotrophe subsect. Nipponocirsium (Compositae), with a new species from Taiwan - Chih-Yi Chang; Pei-Chun Liao; Hsy-Yu Tzeng; Junko Kusumi; Zhi-Hui Su; Yen-Hsueh Tseng (Botanical Studies)
Abstract Background This study explored chromosome number variation, phylogenetic divergence, and mechanisms underlying speciation in East Asian thistle Cirsium Mill. sect. Onotrophe (Cass.) DC. subsect. Nipponocirsium Kitam. (Compositae). The study focused on the newly identified species from Taiwan: Cirsium pengii Y.H. Tseng, P.C. Liao & Chih Y. Chang. Utilizing phylotranscriptomic data to reconstruct evolutionary relationships between the Taiwanese and Japanese taxa of Cirsium subsect. Nipponocirsium as well as their divergence times and chromosomal characteristics. Additionally, the chromosome number, morphology, and pollen morphology of the unknown Cirsium taxon are compared with other known subsect. Nipponocirsium taxa from Taiwan. Results Phylotranscriptomic analysis reveals a division within subsect. Nipponocirsium into Japanese and Taiwanese clades. In the Taiwanese clade, C. pengii is basal, while C. tatakaense remains monophyletic with other Taiwanese species despite higher genetic diversity. The prevalent chromosome number in this subsection is tetraploid (2n = 4x = 68), common in Japanese taxa, while Taiwanese members have 2n = 4x = 64. Notably, C. pengii has a diploid number (2n = 32), indicating descending dysploidy followed by polyploidization in Taiwan. This polyploidization, driven by glaciations, likely shaped the evolution of Nipponocirsium. Divergence time estimates suggest the separation of Japanese and Taiwanese clades around 0.74 million years ago (Myr) during glacial periods. Cirsium pengii diverged around 0.47 Myr, while tetraploid species C. kawakamii and C. tatakaense diverged around 0.35 Myr. These species likely evolved in separate refugia, with distinct species boundaries confirmed through species delimitation analysis, karyotype, morphology, and pollen morphology comparisons. Conclusions These findings enhance our understanding of chromosomal evolution and speciation within subsect. Nipponocirsium and underscore the importance of integrating transcriptomic data in phylogenetic studies. This study provides a comprehensive framework for further investigations into the genetic diversity and adaptive mechanisms of this ecologically vital group.